Central core of uprolides D and E: a survey of some ring closing metathesis approaches - Ramana, C. V.; Salian, Sumanth R.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A preliminary study dealing with the feasibility of ring closing metathesis and ene-yne ring closing metathesis to construct the central bicyclic cores of uprolides D and E was investigated. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cembranolides; ene-yne metathesis; Ring closing metathesis; Sharpless asymmetric epoxidation; uprolides D and E